Small is beautiful: restoring degraded lands, one parcel at a time. - Elias, Marlène; Vinceti, B. (Bioversity International and the International Center for Tropical Agriculture, 2016)
The Aichi Biodiversity Targets agreed in Nagoya in 2012 included restoring 15% of the world’s degraded ecosystems by 2020 (Target 15). Subsequent assessments have led to estimates that for terrestrial ecosystems, this 15% means restoring a staggering 350 million hectares – and requires billions of tons of tree seed and trillions of seedlings.